HUBUNGAN PEMBENTUKAN KARAKTER DI KELUARGA DAN DI SEKOLAH DENGAN PRESTASI BELAJAR ANAK DI SEKOLAH DASAR BERBASIS AGAMA ISLAM DAN BUDHA SEKOTA MADYA MEDAN - SIANTURI, SUTRISKA (Jurnal Ilmiah Aquinas, 2019)
This research is aimed to know the correlation of the Character Building in Family and School to the Child’s Learning Achievement at the Elementary School Based on the Muslims and Budha Religion in the City of Medan. This is a correlation research using quantitative approach. The population used in this research are grades four and five pupils of the elementary school based on Muslim and Budha religion in the city of Medan with the total of six hundred pupils. The sampling quota was used in sampling process. Datas in this research were obtained by using character building questionnaire in families and school. The analysis technique in this research is using Statistic Program For Social Science (SPSS). The calculation result showed that the answer of the respondents about the five aspects; religion, honesty, dicipline, social solidarity and responsibility proved that the character building of pupils in the family and school correlates to pupils learning achievement.